Heterogeneous treatment effects of Cerebrolysin as an early add-on to reperfusion therapy: post hoc analysis of the CEREHETIS trial - Kalinin, Mikhail N.; Khasanova, Dina R. (Frontiers in Pharmacology, 2024)
Background There has been intensive research into enhancing the effects of reperfusion therapy to mitigate hemorrhagic transformation (HT) in stroke patients. Using neuroprotective agents alongside intravenous thrombolysis (IVT) appears a promising approach. Cerebrolysin is one of the candidates since it consists of neuropeptides mimicking the action of neurotrophic factors on brain protection and repair. Objectives We looked at treatment effects of Cerebrolysin as an early add-on to IVT in stroke patients with varying HT risk. Methods It was post hoc analysis of the CEREHETIS trial (ISRCTN87656744). Patients with middle cerebral artery infarction (n=238) were selected from the intention-to-treat population. To stratify participants according to their HT risk, the DRAGON, SEDAN and HTI scores were computed for each eligible subject using on-admission data. The study endpoints were any and symptomatic HT, and functional outcome measured with the modified Rankin Scale (mRS) on day 90. Favorable functional outcome (FFO) was defined as an mRS≤2. The performance of each stratification tool was estimated with regression approaches. Heterogeneous treatment effect analysis was conducted using techniques of meta-analysis and the matching-smoothing method. Results The HTI score outperformed other tools in terms of HT risk stratification. Heterogeneity of Cerebrolysin treatment effects was moderate (I2, 35.8%-56.7%; H2, 1.56-2.31) and mild (I2, 10.9%; H2, 1.12) for symptomatic and any HT, respectively. A significant positive impact of Cerebrolysin on HT and functional outcome was observed in the moderate (HTI=1) and high (HTI≥2) HT risk patients, but it was neutral in those with the low (HTI=0) risk. In particular, there was a steady decline in the rate of symptomatic (HTI=0 vs HTI=4: by 4.3%, p=0.077 vs 21.1%, p<0.001) and any HT (HTI=0 vs HTI=4: by 1.2%, p=0.737 vs 32.7%, p<0.001). Likewise, an mRS score reduction (HTI=0 vs HTI=4: by 1.8%, p=0.903 vs 126%, p<0.001) with a reciprocal increase of the fraction of FFO patients (HTI=0 vs HTI=4: by 1.2% p=0.757 vs 35.5%, p<0.001) was found. Conclusion Clinically meaningful heterogeneity of Cerebrolysin treatment effects on HT and functional outcome was established in stroke patients. The beneficial effects were significant in those whose estimated on-admission HT risk was either moderate or high.